Research on Fatigue Stability of Rocket Launcher High Thrust Electro-mechanical Servo Actuator - Jianxin Zhang; Wenzhu Deng; Wei Lei (Jixie chuandong)
The high thrust electro-mechanical servo actuator in rocket launcher is a linear transmission mechanism with high precision planetary roller screw as its core component. In order to study the fatigue stability characteristics of planetary roller screw mechanism，a fatigue comparison test of fault-free and fault is carried out. Based on the test data curve，the influence of loss of gear tooth and two working conditions with or without grease on load，displacement，speed and temperature rise of planetary roller screw mechanism are analyzed. The result shows that planetary roller screw mechanism could maintain relatively stable load，displacement，speed and temperature rise curves under two working conditions of partial tooth defect or without grease. The planetary roller screw mechanism of high thrust electro-mechanical servo actuator could be used without maintenance or less maintenance for the engineering application in case of tooth damage and little grease.